Religion and Children’s Rights (Human Rights – Children’s Rights, 2025)
The book “Religion and Children’s Rights” explores the relationship between religion and children’s rights, offering a comprehensive examination of the rights of the child in religious contexts. It analyses the international and domestic challenges to implementing children’s rights in these contexts, while addressing contemporary issues at the intersection of religion and children’s rights. Although religion profoundly shapes the lives of children, its role has received little attention in the scholarly literature on children’s rights, partly because questions concerning children’s freedom of religion and belief are often highly sensitive and controversial. This volume seeks to fill that gap, by shedding light on the place of religion within the normative framework of the UN Convention on the Rights of the Child and providing the readers with a deeper understanding of children’s rights in religious contexts. The book is divided into three parts. The first part provides a general introduction and conceptual framework for examining children’s religious human rights, as well as examines international standards of child protection against abuse and harmful religious practices. The second explores issues concerning the protection of children’s religious identity in different settings, including the family, schools and alternative care, while also addressing the specific needs of children belonging to indigenous peoples and national minorities. The third part examines safeguarding policies in selected Christian churches. A central issue animating the third part is the approach and role of the main religious communities in Central and Eastern Europe in protecting children against violence, while highlighting the added value of engaging religious communities in promoting and protecting children’s rights. This volume is intended as a valuable resource for scholars, legal practitioners, policymakers and other professionals working with children and dealing with children’s rights in their everyday practice or academic research.